Princípio da colaboração: o novo direito processual civil à luz do estado democrático - Ribeiro, Olívia Guimarães (2016)
The contemporary Civil Procedure Law goes through a profound phase of structural modifications, which have proved essential given the need to constantly adapt the rules to the evolution occurring in society. The issue of a new Civil Procedure Code entered into force in March this year, shows that the mere holding of mini reforms to adjust the procedural law to arising social needs no longer showed efficient, making it necessary the introduction of a completely new instrument in the legal system, which emerged with the values of these transformations. The new civil procedural law is set up, so a complete work, prepared under a completely different perspective of the former. The fact is that society has evolved, and with it, the way of looking, reflect and evaluate everyday situations. The principles and values of people have changed and, in the meantime, the need arose to build a new civil procedural law, tied to constitutional principles and guided by new guidelines, no longer conceived as a mere instrument or adjective material law. Among the principles established by the new Codex in its introductory part, played most of the Federal Constitution, there is the principle of collaboration, whereby the subjects of procedural relationships should cooperate so that the collimated end is reached, with subsequent delivery of judicial services effective. Even before the entry into force of the new Civil Procedure Code the principle is already causing debate among processualist, which differ in perquire the feasibility of cooperation between litigants, given the antagonism of their interests. This work is guided in the statement that the principle of collaboration goes beyond the mere relationship between the parties, dealing with all procedural subject, so that both statecourt as parties should contribute to the procedural motion has a development satisfactory, so as to enable effective delivery of judicial services in each case.